2014
DOI: 10.1364/boe.5.000817
|View full text |Cite
|
Sign up to set email alerts
|

Assessing blood coagulation status with laser speckle rheology

Abstract: Abstract:We have developed and investigated a novel optical approach, Laser Speckle Rheology (LSR), to evaluate a patient's coagulation status by measuring the viscoelastic properties of blood during coagulation. In LSR, a blood sample is illuminated with laser light and temporal speckle intensity fluctuations are measured using a high-speed CMOS camera. During blood coagulation, changes in the viscoelastic properties of the clot restrict Brownian displacements of light scattering centers within the sample, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 57 publications
0
87
0
Order By: Relevance
“…Laser speckle rheology (LSR) is a powerful optical tool for evaluating the viscoelastic properties of materials with many applications in polymer engineering, food sciences, and biomedical imaging [17]. The viscoelastic behavior of a material is usually described by the viscoelastic modulus, G * ( ω ), and is often measured by a mechanical rheometer, in which a specimen is sheared between two parallel plates in an oscillatory manner, and the ratio of the exerted stress to the resulting strain is calculated.…”
mentioning
confidence: 99%
“…Laser speckle rheology (LSR) is a powerful optical tool for evaluating the viscoelastic properties of materials with many applications in polymer engineering, food sciences, and biomedical imaging [17]. The viscoelastic behavior of a material is usually described by the viscoelastic modulus, G * ( ω ), and is often measured by a mechanical rheometer, in which a specimen is sheared between two parallel plates in an oscillatory manner, and the ratio of the exerted stress to the resulting strain is calculated.…”
mentioning
confidence: 99%
“…These large scattering particles then contribute mainly to the non-fluctuating component of the speckle pattern, which adjusts the g 2 ( t ) plateau level, and represents the elastic behaviour of the clot. The elasticity of the clot, implicated in the plateau level, provides key diagnostic information as it closely correlates with fibrinogen concentration of blood in patients [40]. Thus, due to confinement of larger particles at later stages of coagulation, diffusely moving smaller particles are expected to contribute more to the estimated MSD [17].…”
Section: Discussionmentioning
confidence: 99%
“…Results of our recent studies have demonstrated a close correlation between coagulation metrics measured using laser speckle approaches and clinically-relevant CCT results such as aPTT, PT, and fibrinogen level [40]. In the future, we envision that OTEG may be performed using a test strip with a single drop of blood obtained using a finger-stick method.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 On the other hand, microfluidic constriction-based optical detection methods utilize flow rate change of blood in a microfluidic channel by clot formation. 7 The readout is usually performed with simple optical sensors.…”
Section: Introductionmentioning
confidence: 99%